KONSTRUKSI YURIDIS TERHADAP PERTIMBANGAN MAJELIS HAKIM DALAM PUTUSAN NOMOR 46/PID.SUS/2021/PN.SRG BERDASARKAN PERATURAN PERUNDANG -UNDANGAN - Fidri Sadri; Juanda; Dwi Atmoko (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The crime of money laundering does not stand alone because the assets placed, transferred, or diverted by way of integration were obtained from the crime, meaning that there was already another crime that preceded it (predicate crime). There are 26 (twenty-six) types of predicate crimes obtained from the proceeds of money laundering crimes as stipulated in Article 2 Paragraph (1) of Law No. 8 of 2010. Basically, these activities consist of three steps, each of which stands alone but is often done together, namely placement, layering, and integration. Moreover, the crime of money laundering is closely related to financial, economic, banking, investment, juridical issues, and even social and political issues that have national and even global impacts as found in the case with Decision Number 46/Pid.Sus/2021/Pn. Srg.The research method used in this study is a normative juridical research method using a statutory approach. Based on the results of the research, it can be seen that the juridical construction is considered by the judge in deciding case number 46/Pid.Sus/2021/Pn. Srg namely by paying attention to the elements contained in the articles used by the public prosecutor in the indictment. When viewed based on legal principles, the application of these articles is appropriate for the crimes committed by the defendants, but based on the principle of justice, the decisions issued by the Panel of Judges are deemed not to be able to fulfill a sense of justice, because the victims do not receive complete compensation in accordance with with the losses they suffered, as well as the confiscation of evidence of economic value, it was felt that they did not fulfill a sense of justice because the state in this case did not suffer any losses.